2016
DOI: 10.3386/w22277
|View full text |Cite
|
Sign up to set email alerts
|

Private Provision of Social Insurance: Drug-specific Price Elasticities and Cost Sharing in Medicare Part D

Abstract: Standard theory suggests that optimal consumer cost-sharing in health insurance increases with the price elasticity of demand, yet publicly-provided drug coverage typically involves uniform cost-sharing across drugs. We investigate how private drug plans set cost-sharing in the context of Medicare Part D. We document substantial heterogeneity in the price elasticities of demand across more than 150 drugs and across more than 100 therapeutic classes, as well as substantial heterogeneity in the cost-sharing for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 34 publications
3
49
2
Order By: Relevance
“…We also find effects for “other” admissions. While the clinical linkages between greater prescription drug use and these “other” conditions are not as well known, as compared to certain illnesses such as cardiovascular disease, there is evidence that Part D increases use of all therapeutic classes of drugs (Khan and Kaestner, 2012) and that the “price” elasticity of demand for prescription drugs are relatively similar for chronic and nonchronic treatments (Einav, Finkelstein, and Polyakova, ). So, it is plausible that hospitalizations for “other” illnesses declined, consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…We also find effects for “other” admissions. While the clinical linkages between greater prescription drug use and these “other” conditions are not as well known, as compared to certain illnesses such as cardiovascular disease, there is evidence that Part D increases use of all therapeutic classes of drugs (Khan and Kaestner, 2012) and that the “price” elasticity of demand for prescription drugs are relatively similar for chronic and nonchronic treatments (Einav, Finkelstein, and Polyakova, ). So, it is plausible that hospitalizations for “other” illnesses declined, consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…For each enrollee, we estimate counterfactual costs in each plan (after discarding very small plans) holding consumption constant. Although Einav, Finkelstein, and Polyakova (2016) have shown that moral hazard affects an enrollee's drug consumption and, in addition, an enrollee might be elastic across therapeutic substitutes when she changes plans, dealing with these issues is beyond the scope of the current article. We follow the existing literature in our calculation of 12 It may be that over time, employers and their about-to-be-retired employees no longer make other arrangements for pharmaceutical coverage, but build in to the employee benefit that he or she will use Part D. An evolution of this type would cause the flow rate into Part D at retirement to increase over time.…”
Section: Datamentioning
confidence: 99%
“…It is also the metric CMS uses to approve plans and calculate each region's benchmark. Other aspects of the plan's strategy such as the design of the formulary (which, as noted, is quite tightly regulated) or gap coverage options are important areas for research (see, e.g., Carey, 2017;Einav, Finkelstein, and Polyakova, 2016;Lavetti and Simon, 2016) but are beyond the scope of the current article.…”
Section: The Supply Side Of the Part D Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…Finkelstein and McKnight (2008) and Engelhardt and Gruber (2011) do assess the welfare implications of moral hazard and risk reduction, but they apply separate models to assess the changes in moral hazard and risk reduction, and the associated welfare effects. This approach may be too rough to find an optimal scheme: we prefer to assess these changes simultaneously.Closely related are also Besley (1988) and Goldman and Philipson (2007) who show theoretically the relation between the optimal co-insurance rate and the price elasticity of demand, and Einav, Finkelstein and Polyakova (2016) who present empirical evidence for this relationship in the case of prescription drugs. Also related is the work of Drèze and Schokkaert (2013) on the optimality of deductibles when demand for health care is subject to ex post moral hazard, and Blomqvist (1997) on optimal nonlinear health insurance schemes.…”
Section: Introductionmentioning
confidence: 85%